Experimental and theoretical aspects of crack assisted failures of metallic alloys in corrosive environments – A review. (2022) - Alqahtani, Ibrahim M.; Starr, Andrew; Khan, Muhammad
Abstract: Failure analysis is one of the complex tasks in engineering materials since it involves analyses of the interdependency of factors like environmental conditions, materials properties and loading conditions etc., causing catastrophic failure of engineering components in real-time applications. In recent times, the advances in characterization techniques have led to the precise findings of the cause of the failures in several cases. However, specific failure analysis-based case studies report that the couple load effects of two or more parameters influencing the failures of engineering components are complex to identify. Moreover, it is difficult to formulate a mathematical model involving the interdependency factors to study the failure behaviour of the engineering materials. Especially in aerospace industry, the crack initiation and propagation in metallic alloys are more complex since the various factors like environmental conditions combined with loading parameters cause unpredictable failures. Hence, there is a need to study the effect of environmental conditions combined with different loading systems on the crack propagation of metallic alloys. The review concludes that still a comprehensive analytical modelling approach is required to relate the interdependencies of couple loads such as humidity and temperature of metallic alloys in corrosive environment.